2016
DOI: 10.1155/2016/8096082
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of General Strike on Government Healthcare Delivery in Kerala State in India

Abstract: General strike (also known as hartal) is used as a mode of protest by organizations and political parties in India. It is generally thought that hartals negatively impact the healthcare delivery in a society. We used the Right to Information Act to obtain data from government health centers in Kerala state in India for four hartal days (H-day) and two control days (A-day and B-day) for each H-day, from sixteen health centers including 6 Community Health Center (CHC), 6 Secondary Health Center (SHC), and 4 Tert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…En la visión de las personas entrevistadas la paralización de labores de funcionarios públicos que repercute directamente en los principios de oportunidad y continuidad en la entrega de pres-taciones de salud. Las condiciones de movilización o huelga son una situación constante en el sector salud especialmente en los países de más bajos ingresos, y afecta el principio de continuidad y las garantías en el acceso y oportunidad 32,33 . Algunos estudios demuestran que se generan efectos en la cantidad de prestaciones que se otorgan durante estos períodos y, de manera específica, disminución de consultas y controles de atención primaria 34,35 .…”
Section: Discussionunclassified
“…En la visión de las personas entrevistadas la paralización de labores de funcionarios públicos que repercute directamente en los principios de oportunidad y continuidad en la entrega de pres-taciones de salud. Las condiciones de movilización o huelga son una situación constante en el sector salud especialmente en los países de más bajos ingresos, y afecta el principio de continuidad y las garantías en el acceso y oportunidad 32,33 . Algunos estudios demuestran que se generan efectos en la cantidad de prestaciones que se otorgan durante estos períodos y, de manera específica, disminución de consultas y controles de atención primaria 34,35 .…”
Section: Discussionunclassified
“…And all PHIs (except medical colleges and regional hospitals) are under the control of the respective tiers of the local government. A study conducted using secondary data for the period of 1991–2011 and primary data for 2011–2012 concluded that wherever there was a good relationship between elected representatives of local self-government and health personnel, the system of dual controls and responsibilities yielded good results, and, in most districts, the relationship was cordial and productive (Jacob, 2012; Jacob & Jacob, 2016).…”
Section: Role Of the Village-level Governmentmentioning
confidence: 99%
“…LSGs have steered the coordination of efforts and activities by volunteers [24]. There is journalistic and anecdotal information suggesting that Kerala's COVID response included formal and informal mechanisms comprising a host of players including Kudumbashree (Kerala's government-run women's SHG program), voluntary organisations, youth associations as well as new formations like the Rapid Response Team (RRT) at the ward level set up during the pandemic [25]. RRTs were constituted formally by the state mechanism to have a supervised and monitored support for the state pandemic mitigation efforts [26].…”
Section: Introductionmentioning
confidence: 99%